Validation of CRISPR activation system in Aedes cells using multicistronic plasmid vectors - Jaiswal, Vijeta; Varghese, Sara Ashok; Ghosh, Sanjay (Frontiers in Bioengineering and Biotechnology, 2023)
Aedes mosquitoes transmit several pathogens including flaviviruses to humans which result in high morbidity and mortality. Owing to adaptability and climate change, these mosquito vectors are predicted to establish in new geographical areas thus exposing larger populations to the risk of infection. Therefore, control of Aedes vector is necessary to prevent disease transmission. Recently, genetic approaches to vector control have shown promise; however, the tools and methods for manipulating the mosquito genome are rather limited. While CRISPR-Cas9 system has been adapted for gene editing purposes in Aedes mosquito, the dCas9-based transcription control of genes remain unexplored. In this study we report implementation of the CRISPR activation system in Aedes cells. For this we designed, constructed and tested a bipartite plasmid based strategy that allows expression of the dCas9-VPR and targeting guide RNA together with a reporter cassette. Quantitative analysis of the fluorescent reporter gene levels showed a robust over-expression validating CRISPR activation in Aedes cells. This strategy and the biological parts will be useful resource for synthetic transcription factor based robust up regulation of Aedes genes for application of synthetic biology approaches for vector control.